Formulation of water-soluble Buddleja globosa Hope extracts and characterization of their antimicrobial properties against Pseudomonas aeruginosa - Araya, Nicolas; Leiva-Soto, Martín A.; Bruna, Maria V.; Castro-Munoz, Almendra; Behrend-Keim, Beatriz; Moraga-Espinoza, Daniel; Bahamondez-Canas, Tania F. (Frontiers in Pharmacology, 2022)
Buddleja globosa Hope (BG) extracts are traditionally used to treat skin and gastric ulcers due to their healing properties. Non-aqueous solvents such as ethanol and DMSO are usually used to extract naturally occurring compounds. However, the cytotoxicity of these solvents and the low water-solubility of the extracted compounds can hinder their biomedical applications. To overcome the limited solubility of the BG extracts, we aimed to enhance the solubility by processing a standardized hydroalcoholic extract (BG-126) through spray drying (SD), with and without two solubility enhancers. Spray dried BG extract (BG-SD) and spray dried BG extracts plus polyvinylpyrrolidone (BG-SD PVP) and Soluplus® (BG-SD SP) were developed starting from BG-126 (containing 53% ethanol). These four formulations were characterized by total phenolic content, water solubility at 25 and 37 °C, and antimicrobial properties against Pseudomonas aeruginosa. All the SD formulations presented a solubility that allowed to reach maximum concentrations of 1024 µg/mL catechin for BG-SD and 2048 µg/mL catechin for BG-SD PVP and BG-SD SP for antimicrobial testing. BG-SD showed the highest antimicrobial potency with a minimum inhibitory concentration (MIC) of 512 µg/mL catechin, followed by BG-126 with a MIC of 1024 µg/mL catechin and SP. BG-126 also showed to inhibit biofilm formation as well as the excipients PVP and SP. Spray dried BG extract (BG-SD) represents a promising natural active with enhanced antimicrobial properties against P. aeruginosa for further research and development of novel phytopharmaceuticals.